Case Study: Papaya Waste in Different Points of Sale in the Central Region of Veracruz, Mexico - Saez-Tonacca, L (UNIV SANTIAGO DE CHILE, 2025)
The central area ofthe state of Veracruz supplies papaya to both the region and the country. There are few studies on the waste of fruit in sales places. Analyzing this waste is important to propose strategies to reduce it. The objective of this work was to analyze the waste derived from the marketing of this fruit in various points of sale in the central area of the state of Veracruz. To achieve this, a questionnaire was applied to 61 merchants from markets, supply centers, and roadside sales points according to information collected in the first phase. It was found that the main cause of waste is the ripening of the fruit. Interviewees also mentioned that the wasted fruits had fungal damage. We found significant differences between what respondents call waste and what is officially called waste. Therefore, we calculate a "corrected" waste percentage. Roadside points of sale recorded the highest percentage of "corrected" waste since it is used for animal feed. 11.47% of the papaya sold weekly was destined for landfills, which denotes the high level of waste in the studied area.